Structured Approach to Enhance the Quality of Undergraduate Capstone Project: A Case Study - Pawar, Rajendra; Patil, Sachin (Journal of Engineering Education Transformations, 2021)
The capstone project course has been considered as a commanding student-centered learning activity designed to provide an opportunity to an undergraduate student to solve critical real-life problems by applying the technical and soft skills acquired. A major objective of the capstone project is to apply real-life engineering practices to fulfill customer needs. This paper outline the challenges and best practices learned in the development and implementation of the open-ended undergraduate capstone project with the intention to enhance the quality and learning outcomes. In order to enhance the quality of the capstone project, various strategies such as group formation, student evaluation, sourcing student projects, project plan, project space, project funding, and support for patent and paper publications have been discussed also. The capstone project is offered in the fourth year of B. Tech. mechanical engineering program and it consists of two modules; Phase I and Phase II. Around 72 students and 18 supervisors were involved in the activity for the entire academic year. The student learning outcomes were measured using the commercial software and observed that all the learning outcomes have been attained more than 75% and students have developed very good projects in a team by applying technical knowledge and soft skills learned in the program.